Increased safety in periodontal surgery: Doppler ultrasound for detection of relevant palatal blood vessels - a proof-of-concept and cross-sectional study - Bartha, Valentin; Grünfeld, Dan; Kopunic, Aleksandra; Klein, Christian; Wolff, Diana; Ratka-Krüger, Petra; Woelber, Johan Peter; Meller, Christian (Journal of clinical periodontology, 2024)
Aim To evaluate the suitability of a Doppler ultrasound probe in detecting the greater palatine artery or its greater branches non-invasively. Materials and Methods The palatal mucosa of 108 participants (median age 34 years, 51 female) was systematically divided into transversal sectors, each aligning with the positions of the upper molars (M), premolars (P) and canine teeth (C), aiming to facilitate precise and consistent localization of the detected palatal blood vessel across different patients. Blood flow of the palatal blood vessels, presumably, was located by scanning the palatal vault bilaterally using an 8-MHz ultrasound probe linked to a transducer. The distance to the corresponding tooth was measured using a millimetre-scale periodontal probe. Results Within the regions of M2 to P1, the ultrasound transducer gave a delimitable acoustic pulse signal in 80%-98% of all measurements. The measured median distances between the determined position of the artery and the corresponding teeth ranged from 13 to 15 mm, with smaller distances in the anterior region. In several sectors, the distance was significantly higher for men (C: p = .048; P1: p = .041, M1: p < .01; M2: p = .034). Conclusions Use of the Doppler ultrasound transducer might be a promising approach to non-invasively detect relevant palatine blood vessels preoperatively. It, therefore, might have the potential to reduce the risk of accidental injury during palatal surgery.
Zuerst veröffentlicht: 20. März 2024
Gesehen am 29.07.2024